2020
DOI: 10.1136/bmjpo-2019-000628
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of neonatal resuscitation skill retention in frontline healthcare facilities in Bihar, India, after PRONTO simulation training

Abstract: BackgroundUse of simulation in neonatal resuscitation (NR) training programmes has increased throughout low-income and middle-income countries. Many of such programmes have demonstrated a positive impact on NR knowledge and skill acquisition along with reduction of early neonatal mortality and fresh stillbirth rates. However, NR skill retention after simulation programmes remains a challenge.MethodsThis study assessed facility level NR skill retention after PRONTO International’s simulation training in Bihar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…They performed all steps of NRP correctly after training, in line with the previous study. 15,16 This study evaluated the feedback of intern doctors in the form of reflective writing post-NRP and post-observership. Most of the intern doctors had a positive impact of NRP and observership on skill of NRP.…”
Section: Discussionmentioning
confidence: 99%
“…They performed all steps of NRP correctly after training, in line with the previous study. 15,16 This study evaluated the feedback of intern doctors in the form of reflective writing post-NRP and post-observership. Most of the intern doctors had a positive impact of NRP and observership on skill of NRP.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study to determine retention of knowledge and skills after standardized "skills and drills" training in EmONC in Ghana, Kenya, Malawi, Nigeria, Sierra Leone, and Tanzania, showed that after training the mean (95% CI) relative improvement in knowledge was 30.8% (29.1% -32.6%) and 59.8% (58.6%-60.9%) for skills (40). In addition, skill reacquisition with peer-facilitated simulations has been shown to improve neonatal outcomes such as administering effective positive pressure ventilation and assessing infant heart rates increased signi cantly (41).…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, como fragilidades é possível observar a falta de habilidade entre os profissionais da linha de frente (Higgins, et al, 2020), a escassez de conhecimento em fisiologia neonatal e condutas assistenciais (Kunikata, et al, 2015), todavia habilidades de ventilação com máscara facial que foram consideradas fracas, conforme pesquisa realizada com objetivo em determinar se o uso de um monitor de função respiratória (RFM) durante o treinamento de ventilação com máscara com um manequim reduz o vazamento da máscara facial em RN (O' Currain, et al, 2019), constituindo assim uma necessidade de educação continuada (Charafeddine, et al, 2015).…”
Section: Discussionunclassified
“…• Conhecimento do algoritmo de ressuscitação e competência técnica na realização da ventilação por pressão positiva (VPP) (Higgins, et al, 2020).…”
unclassified